Workplace Digitalization in Public Sector Organization Towards Operational Effectiveness: Current Landscape, Issues and Challenges - Nasution, Shafira Tasyani; Damayanti, Dida Diah; Julian, Widia; Abu Bakar, Nur Azaliah; Deraman, Zakaria; Tarmiji, Mohamad Fadzli; Yusoff, Rohani; Kama, Nazri (International Journal of Innovation in Enterprise System, 2020)
To date, public sector organisation begin to implement the digital workplace as part of their digital government initiative but yet there is proven the success of its implementation and how it impacts the government operation effectiveness. Therefore, based on a Technology-Organization-Environment (TOE) framework, this paper aims to investigate the current landscape, issues and challenges in workplace digitalization in public sector organization. A comparative analysis of the digital workplace approach was performed on nine Malaysian Public Sector organisations of the various business core function. This study found that there are nine factors related to digital workplace implementation. The main finding revealed that most organisation are not fully optimizing the digital workplace functionality and only using it as a digital repository. Based on this finding, significantly it can contribute the development of a new digital workplace framework for public sector organization in ensuring its contribution to operational effectiveness